LOOK BOTH WAYS! CARRYING LITERATURE AND POETRY FROM ONELANGUAGE TO ANOTHER (Journal of Contemporary Philology, 2025)
The work of the literary translator is a complex process of transporting ideas, sounds, and  images back and forth across languages. In this short paper I explore problems for  translators working from Macedonian into English, systemic impediments to translation, and the development of a translator’s methodology and ethics. Working from my own experiences as a linguist and translator, and the experience of other well-known translators,  I discuss the expanding corpus of works translated from Macedonian, the intersections of literary and linguistic knowledge, with examples from my translations, and the political  implications of translating from Macedonian into English.
Keywords: literary translation; translation theory; ethics of translation; resources for translators